Association between histamine-2 receptor antagonists and adverse outcomes in neonates: A systematic review and meta-analysis - Santos, Victor S. (PLoS One, 2019)
BACKGROUND: The use of histamine-2 receptor antagonists (H(2)RA) in neonates is still debated because of possible risk of infection, necrotizing enterocolitis (NEC) and increased mortality. AIM: To review whether the use of H(2)RA in neonates admitted to neonatal intensive care units (NICU) is associated with infection, NEC or mortality. MATERIALS AND METHOD: We performed a systematic search in PubMed, Web of Science and SCOPUS databases using the terms “histamine-2 receptor antagonists”, “infection”, “necrotizing enterocolitis”, “mortality”, “neonates” and related terms to identify studies published up to April 30, 2017. We included studies conducted in hospitalized neonates and exposed to H(2)RA. The primary outcomes were infection, NEC and mortality. We included reports of infections with clinical signs and positive culture, and NEC according to Bell stages (stage ≥II) based on standardised clinical and radiologic criteria. Among 1,144 studies identified, 10 fulfilled the selection criteria. Information extracted included study design, sample size and number of participants, along with the outcomes of interest. We conducted a meta-analysis of adjusted data and pooled estimates of infection, NEC and mortality are reported as odds ratios (OR) and 95% confidence intervals (95%CI). RESULTS: Ten studies were analysed. There were substantial associations between H(2)RA and infection (pooled OR: 2.09; 95%CI: 1.35–3.24; P = 0.001) and NEC (pooled OR: 2.81, 95%CI: 1.19–6.64; P = 0.02) but not with the mortality risk (pooled OR: 1.76; 95%CI: 0.50–6.16; P: 0.38). CONCLUSION: Current evidence suggests that H(2)RA is associated with an increased risk of infection and NEC, but not with mortality in neonates admitted to NICU. The use of H(2)RA in neonates must be stringently considered when necessary.